Three generations of the administrative procedure and the Polish Administrative Procedure Code - Ćwiklińska, Marta (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
Javier Barnes has distinguished three generations of the administrative procedure. The aim of this essay is to examine the Polish Administrative Procedure Code and some other Polish statutes in terms of those three generations of the administrative procedure. The first generation of the administrative procedure is the oldest one. It is a typical adjudication procedure model where a public authority issues a formal and binding administrative decision addressed to an individually designated addressee, also called command and control in the Anglo-Saxon legal language. The Polish Administrative Procedure Code contains the first generation procedure regulations only. The second generation, i.e. rule-making procedure, is not expressly specified in the Code, though it is present in the Polish administrative law system. There is a number of statutes comprising substantial administrative regulations aiming to protect such values as public safety, health, etc. Unlike in the instance of the first generation, it results in producing an administrative act designed to address a wider and abstractly named audience, instead of a specifically identified legal and/or natural person. The third generation of the administrative procedure consists of making a public policy and implementing the procedure and it is the most complex legal regulation of the administrative activity. The best example of law containing such a sophisticated procedure in Poland is the Act on the provision of information about the natural environment and its protection, public participation in environmental protection and environmental impact assessment (Journal of Laws of 2013, item 1235, as amended) of 3 October 2008.